(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the state of the market of educational services in Uzbekistan and identifies the main directions of its development. The aspects of the interaction of the consumer market with the market of educational services have been identified and recommendations for its development have been given.Education is one of the key components in the concept of human development, and it also plays a key role in solving important problems of society. Throughout human civilization, the high level of development of education and science has been an important driving force of social, technical and economic development.